Ku-band serrodyne frequency translator using wideband MMIC analogue phase shifters - Lucyszyn,S; Pilchen,Y; Robertson,ID; Aghvami,AH (IEEE, 2007)
A novel Ku-band serrodyne frequency translator is presented which employs wideband MMIC analogue phase shifters. The MMICs have a simple topology and are fabricated using low cost foundry processing techniques. The resulting highly nonlinear tuning behaviour of the complete 360° phase shifter is overcome with two different types of modulating signal: the first having a predistorted sawtooth function (using DSP techniques) and the second having a linear sawtooth function (resulting in 20% under-modulation). With an input carrier frequency of 14GHz, the measured results demonstrate high levels of carrier suppression and unwanted sideband suppression, with both functions. This performance was maintained at all carrier frequencies in the 13 to 15GHz frequency range - without having to modify the functions. In addition, 0dB conversion loss was achieved and almost no control power was required.